Water quality variation and screening of microalgal distribution in thachan pond Chidambaram taluk of Tamil nadu - Balakrishnan, Elayaraj; Selvaraju, M. (International Journal of Biological Research, 2014)
A laboratory study was conducted to monitor the water quality and microalgal distribution of Thachan pond, Chidambaram taluk, Cuddalore district, Tamil Nadu, India. The important parameters tested were temperature, pH, turbidity, electric conductivity, total dissolved solids, turbidity, alkalinity, free CO2, dissolved oxygen, chloride, nitrate and phosphate. Microalgal distribution studies were observed. Monthly fluctuations of different seasonal diversity i.e., 35 algal species belongs to four groups viz., Cyanophyceae (41%), Chlorophyceae (27%), Euglenophyceae (14%) and Bacillariophyceae or Diatoms (17%). Among the microalgae Cyanophyceae was found to be dominant group throughout in the study period. Microalgae producing biotoxin such as Microcystis aeruginosa, Chroococcus minor, Oscillatoria curviceps, Oscillatoria tenuis, Anabaena spiroides, Nostoc pruniforme and Aphanocapsa grevillei were recorded in the pond. Pond was found to be moderately polluted and showed a trend of increasing eutrophication. The significant correlations were noted in the different parameters. Keywords: Eutrophication, Microalgal Distribution, Pond Water Quality, Seasonal Diversity.